To spray or not to spray: Impact of phosphite spraying for Phytophthora cinnamomi control on Proteaceae species in southwestern Australia - Michelle Boulle; Barbara A. Stewart; Sarah Barrett (Conservation Science and Practice, 2023)
Abstract Phosphite has been sprayed on threatened natural plant communities in southwestern Australia for the past 25 years to mitigate the impact of the globally widespread plant pathogen, Phytophthora cinnamomi. Of concern is that this may result in an increase in phosphorus concentrations in naturally nutrient deficient soils, causing the loss of plant species that are sensitive to increased phosphorus levels. The impact of aerial spraying phosphite on soil and Proteaceae species richness and abundance was measured at three sites within the Southeast Coastal Province of Western Australia. Healthy and diseased vegetation which had been sprayed with phosphite for 14–26 years was compared with nonsprayed healthy and diseased vegetation. Contrary to expectations, there was no evidence that spraying is doing harm to Proteaceae species at the three sites studied. Healthy‐nonsprayed and Healthy‐sprayed areas had generally similar levels of soil total P, and this was associated with similar values for Proteaceae species richness and abundance in these areas. Phosphite spraying of diseased vegetation benefited Proteaceae plant diversity and abundance by preventing the disappearance of some species. Given these results, it was recommended that phosphite spraying be continued as a management action for controlling Phytophthora cinnamomi while research into alternative solutions continues.